Neuroregenerative and neuroprotective actions of immunophilin ligands in murine models - Daneri Becerra, Cristina del Rosario (2017)
Immunophilins (IMMs) are a family of intracellular proteins that bind immunosuppressive drugs. They are referred to as FK506-binding proteins (FKBPs) when they bind FK506, and cyclophilins (CyPs) when they bind cyclosporine A (CsA). In previous studies performed in cell cultures, we demonstrated that FK506 shows neuroregenerative and neuroprotective actions via FKBPs, the expression balance between FKBP52 and FKBP51 playing a key role during those processes.